MODEL PENGASUHAN BAGI ANAK DIDIK LPKA - Nurendah, Gemala; Musthofa, Muhammad Ariez; Maslihah, Sri (Program Studi Psikologi Universitas Pendidikan Indonesia, 2019)
This study was designed to describe an appropriate parenting model for children in LPKA (Rehabilitation Center for Children). A grounded research approach was utilized and a sample of 15 to 18 year old children inmates amount 56 childrens was interviewed. It was found that family and religiosity concepts are important factors for the children. Parenting model for the children have to involve both religiosity and emotional attachment aspects. The results showed that a suitable parenting model was the concept of religiosity and familyhood. This is obtained through the fostering of religious aspects such as conducting prayer activities in congregation, learning to read Al-Quran, and religious lectures. While the concept of familyhood can be through personal interaction among students and with officers who can build emotional closeness.